IMPACT OF GLOBALISATION ON TEXTILE INDUSTRIES: A CASE STUDY OF SOME NIGERIAN INDUSTRIES IN KANO METROPOLIS - Gatawa, Nasir Mukhtar; Aliyu, C. U.; Musa, Sani (European Scientific Journal, ESJ, 2013)
Using panel data set for 3 selected textile industries in Kano State for the period 1985 – 2005 this study utilized Fixed Effects Regression Model (FEM) and Random Effects Regression Model (REM) to investigate on globalization and textile output in Kano. Results from this research reveal that electricity consumption has significant positive influence on textile output. Another finding of the research is that globalization and exchange rate of naira against United State dollar have negative but significant influence on textile output. The study therefore recommends that Nigerian government should take a second look at her membership of the World Trade Organisation (W.T.O) and selectively engage those policies that will promote her national interest, most especially the imperative need to protect the textile firms. As for the exchange rate, adjustment should be made in the level of the domestic currency based on the interactions of market forces that will facilitate appropriate pricing of the foreign exchange and enhance domestic products which enhance their competitiveness in the export market. Moreover, stable and reliable power supply is necessary to generate optimum production at lower cost so as to enhance utilization of idle resources, expand factor incomes, improve competitiveness and expand overall textile output.